Answer:
False
Explanation:
Multiply both sides by b ÷ c
I know this isn't usual, but there is nothing illegal about it.
(c/a - a/c) = b÷c * b/a Change b÷c to b/c
c/a - a/c = b/c * b/a Combine the right
c/a - a/c = b^2/(ac) Find the numerator using the LCM ac
(c*c - a*a)/(ac) = b^2/(ac) Multiply both sides by ac
c^2 - a^2 = b^2 This may or may not be true. If there is one false case it is not true.
The statement is false.
c = 10
a = 8
b = 6
10^2 - 8^2 = 6^2 This works.
12^2 - 11^2 = 9^2 will not work.